Lenvatinib for Anaplastic Thyroid Cancer - Tahara, Makoto; Kiyota, Naomi; Yamazaki, Tomoko; Chayahara, Naoko; Nakano, Kenji; Inagaki, Lina; Toda, Kazuhisa; Enokida, Tomohiro; Minami, Hironobu; Imamura, Yoshinori; Sasaki, Tatsuya; Suzuki, Takuya; et al. (Frontiers in Oncology, 2017)
Background: Lenvatinib has been approved by regulatory agencies in Japan, the United States, and the European Union for treatment of radioiodine-refractory differentiated thyroid cancer. Thyroid cancer, however, is a clinically diverse disease that includes anaplastic thyroid cancer, the subtype associated with the highest lethality. Effective therapy for anaplastic thyroid cancer is an unmet need. Patients and methods: This phase 2, single-arm, open-label study in patients with thyroid cancer, including anaplastic thyroid cancer, radioiodine-refractory differentiated thyroid cancer, and medullary thyroid cancer was conducted from 3 September 2012 to 9 July 2015. Patients received lenvatinib 24 mg daily until disease progression or development of unacceptable toxicity. The primary endpoint was safety, and the secondary endpoint was efficacy, as assessed by progression-free survival, overall survival, and objective response rate. Results: At data cutoff, 17 patients with anaplastic thyroid cancer were enrolled. All experienced ≥1 treatment-emergent adverse event. The most frequent treatment-emergent adverse events were decreased appetite (82%), hypertension (82%), fatigue (59%), nausea (59%), and proteinuria (59%). Of note, only 1 patient required lenvatinib withdrawal because of a treatment-emergent adverse event, and this treatment-emergent adverse event was considered unrelated to lenvatinib. The median progression-free survival was 7.4 months (95% confidence interval [CI]: 1.7–12.9), the median overall survival was 10.6 months (95% CI: 3.8–19.8), and the objective response rate was 24%. Conclusions: In this study, lenvatinib demonstrated manageable toxicities with dose adjustments, and clinical activity in patients with anaplastic thyroid cancer. This clinical activity of lenvatinib warrants further investigation in anaplastic thyroid cancer.